1982
DOI: 10.2134/agronj1982.00021962007400050018x
|View full text |Cite
|
Sign up to set email alerts
|

Response of Drip‐Irrigated Sugarcane to Drought Stress1

Abstract: Though drip irrigation is used on more than half of the irrigated sugarcane (Saccharum spp. hybrid) in Hawaii, the effects of drought stress on the growth and yield of drip‐irrigated sugarcane has not been investigated extensively. This study reports the effects of a single period of drought stress on the growth and metabolism of cultivar H62‐4671 during vegetative growth in drip‐irrigated fields during the 1st year of a normal 2‐year crop in five fields at Kekaha Sugar Company, Kauai, Hawaii. The plants range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

1983
1983
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 5 publications
(5 reference statements)
0
7
0
3
Order By: Relevance
“…Several authors have described the effects of water defi cits on processes such as leaf expansion and stalk elongation (Hill, 1966;Kingston and Ham, 1975;Jones, 1980;Koehler et al, 1982;Inman-Bamber and De Jager, 1988;Roberts et al, 1990;Nable et al, 1999), leaf senescence (Inman-Bamber and De Jager, 1988;Inman-Bamber, 1994), sucrose content, dry matter (Inman-Bamber and De Jager, 1988) and photosynthesis (Roberts et al, 1990). However, recent studies have shown that tillering and intense growth phases are the most critical to water defi cit, since the most of sugarcane biomass is produced during these periods (Ramesh and Mahadevaswamy, 2000;Inman-Bamber and Smith, 2005).…”
Section: Soil Moisturementioning
confidence: 99%
“…Several authors have described the effects of water defi cits on processes such as leaf expansion and stalk elongation (Hill, 1966;Kingston and Ham, 1975;Jones, 1980;Koehler et al, 1982;Inman-Bamber and De Jager, 1988;Roberts et al, 1990;Nable et al, 1999), leaf senescence (Inman-Bamber and De Jager, 1988;Inman-Bamber, 1994), sucrose content, dry matter (Inman-Bamber and De Jager, 1988) and photosynthesis (Roberts et al, 1990). However, recent studies have shown that tillering and intense growth phases are the most critical to water defi cit, since the most of sugarcane biomass is produced during these periods (Ramesh and Mahadevaswamy, 2000;Inman-Bamber and Smith, 2005).…”
Section: Soil Moisturementioning
confidence: 99%
“…In the Hawaiian cultivar H62-4671, relative SER (RSER, the ratio of SER of stressed to unstressed plants) reduced rapidly as L decreased below −0.6 MPa and was only 0.1 when L decreased below −1.3 MPa (Koehler et al 1982). As L can decrease to −1.0 MPa or less even in well-irrigated plants (Roberts et al 1990), it can be expected that water stress-induced reduction in SER will be difficult to avoid even with frequent irrigation.…”
Section: Water Stressmentioning
confidence: 99%
“…The role of proline in osmoregulation and the contribution of osmoregulation to drought adaptation remain uncertain in sugarcane. Koehler et al (1982) showed a large increase in the concentration of potassium, reducing sugars, and organic acids occurred in the leaf blade during drought but the amount of free amino acids and sucrose remained unchanged. It appears that potassium is the dominant substance involved in osmoregulation in both stressed and nonstressed plants, contributing nearly 65 and 52% of , respectively.…”
Section: Osmoregulation During Water Stressmentioning
confidence: 96%